Perkawinan Campuran antara WNI dan WNA: Tinjauan Yuridis atas Status Kewarganegaraan dan Akibat Hukum di Indonesia - Muhammad, Muhammad (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
Mixed marriages between Indonesian Citizens (WNI) and Foreign Citizens (WNA) are a phenomenon that is increasing along with global mobility. The difference in nationality in marriage raises various legal issues, especially related to citizenship status, the rights and obligations of husband and wife, and the status of children. This research aims to analyze legal problems in mixed marriages, identify the legal consequences caused, and formulate solutions based on the national legal framework that applies in Indonesia. This research uses normative legal research methods with legislative and conceptual approaches. The legal materials used include primary, secondary, and tertiary legal materials obtained through literature studies. The analysis was carried out qualitatively to examine the provisions in Law Number 1 of 1974 concerning Marriage as amended by Law Number 16 of 2019 concerning Marriage, as well as Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia. The results of the study show that the Marriage Law has not comprehensively regulated the consequences of the law on mixed marriage, especially related to legal choices and the common property regime. Arrangements regarding the status of children are regulated through provisions that link citizenship status to applicable law. Meanwhile, the Citizenship Act of 2006 provides more progressive legal protections, notably by removing citizenship provisions that discriminate against women and providing limited dual citizenship recognition for children of mixed marriages. The findings of this study confirm the need for more explicit harmonization of regulations and regulations regarding the legal consequences of mixed marriage to ensure legal certainty and protection for the parties.